The Management of Viengchalern Temple, Xaysetha District, Vientiane Capital - VILAVAN, Monk khounta; NORDALA, Phouvong; SISOMBATH, Sithonh; KEOMANYKA , BOUNCHANH; XUAMOLEE, Thongsy (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The main objectives of this research entitled “The management of Viengchalern temple, Xaysettha district, Vientiane capital” are (1) to study the management of Viengchalern temple, (2) to compare the the management of Viengchalern temple in the general opinions of the people and (3) to study the problems, obstacles and guidelines of the people toward the management of Viengchalern temple, through the survey research. This research was conducted by a survey of 350 people using cluster sampling. The five levels questionnaires were used to collect data for this study. The questionnaires were divided into two sections. The first section had data from open questions, and the second section contained data from closed questionnaires about people's opinions toward the management of Viengchalern temple. For data collection, a rating scale and an open-structured questionnaire with a reliability value of 0.943 were utilized. The data was analyzed using frequencies, percentages, averages, standard deviations, t-tests, f-tests, and one-way analysis of variance, and the one-way anova was compared. The results of this research found that people have an opinion on the management of Vat Vieng Chaleun as a whole at many levels and each aspect at many levels, the results of comparing the opinions of the people on the administration of Vat Viengchaleun were classified according to their personal status by sex, age, education level and occupation. It was found that there were statistically significant differences at the level of 0.05, and Guidelines for improving the administration of Viengchaleun Temple as a whole: The administration of the temple should be decentralized to those involved in the administration to make the administration of the temple and the administration more efficient, there should be a meeting of all parties, both monks and people, and help each other to build a good relationship. There should be a policy of the temple plan to clearly indicate the positions and responsibilities of the personnel. Scholarships should be promoted for monks and nuns who are willing to study both secularly and religiously, as appropriate, in order to become important personnel in the afterlife. Courses should be opened for the training and dissemination of Buddhism to monks and nuns within temples and other places. There should be performances of sermons and commentary on the basis of sermons or lectures. The construction and restoration of the building and property of the temple should be the maintenance, repair and decoration of the existing material walls and monuments to make them permanent and additional construction to suit the national art and culture and should be built as necessary for the preservation of the temple.